Analysis of Melamine Using Electronic Nose, Gas Chromatography-Time of Flight - Mass Spectrometry and High Performance Liquid Chromatography - Rohman., Abdul; Che Man, Yaakob B.; Hafidz, R. M. (Journal of Food and Pharmaceutical Sciences, 2013)
An  electronic  nose  (E-Nose)  has  been  used  as  rapid  analytical  technique  for  melamine detection  in  food  samples.  The  parameter  used  is melamine  retention  index  (MRI)  in  E-Nose  chromatogram.  The  value  of MRI  was  also  confirmed  using  two  dimensional  gas chromatography-time of flight-mass spectrometry (GCxGC-TOF-MS). The value of MRI using E-Nose and GCxGC-TOF-MS was nearly close  i.e 1486 and 1540 respectively. HPLC has been used  for  quantitative  analysis  of melamine  in  some milk  products  suspected  to  contain melamine using column Nova-Pak® C18;(150 x 3.9 mm  i.d; 4 µm) at 30°C. The mobile phase was  5 mmol  L−1  NaH2PO4  delivered  isocratically  at  flow  rate  of  1 mLmin-1 . Melamine was linear at concentration range of 0.0625 – 50.0 µg/ml with coefficient of determination (R2 ) of 0.999.